Consumer Perception on Aspects of The Think & Act Experience at The Gacoan Noodle Restaurant Gatot Subroto, Bandung City - Annisa Nur Rohmayanti; Siti Zakiah; Umi Sumarsih (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study discusses consumer perceptions of the Thinking and Acting experience at the Gacoan Gatot Subroto Noodle Restaurant, Bandung City. Think is an experience that demands intelligence to create cognitive experiences and problem-solving by involving consumers creatively; the Act is designed to create consumer experiences that are related to the physical body. Customer Experience is a big key in a business or company; Customer Experience depends on the service provided to customers by a company. Customer Experience is simply a process, strategy, and new implementation of a company to manage customers in customer experience with a product or service from a company. In this study, the authors discuss